The Relationship Between Reading Interest With Learning Outcomes Elementary School Students - Azizah; Hasanah, Uswatun (LPPM Universitas Tadulako, 2021)
This study aims to determine the relationship between reading interest and students' Indonesian learning outcomes. This type of research uses quantitative methods with a correlation research design. This research was conducted in the fourth grade of SD Inpres 1 Donggulu. The instruments used in this research are questionnaires and documentation. The data analysis technique used is descriptive statistics, normality test, product moment correlation and coefficient of determination (KD). The results showed that reading interest was in the strong category and Indonesian language learning outcomes were in the very good category. The results of the calculation of the product moment correlation show that rcount > rtable (0.511 > 0.468), then Ha is accepted and H0 is rejected, meaning that there is a significant relationship between reading interest and Indonesian language learning outcomes for fourth grade students of SD Inpres 1 Donggulu. The relationship between reading interest and Indonesian language learning outcomes for fourth grade students of SD Inpres 1 Donggulu has a moderate level of relationship and if it is presented it is 26%, while the remaining 74% is influenced by other factors.